A preliminary investigation on the relationship between gut microbiota and gene expressions in peripheral mononuclear cells of infants with autism spectrum disorders. Issue 12 (1st December 2016) - Inoue, Ryo; Sakaue, Yuko; Sawai, Chihiro; Sawai, Toshihiro; Ozeki, Motoyuki; Romero-Pérez, Gustavo A.; Tsukahara, Takamitsu
Abstract : Fecal and blood samples of infants with autism spectrum disorders (ASD) and healthy infants were analyzed to investigate the association of altered gut microbiota and ASD development. 16S rRNA gene-based sequencing found that, unlike those of healthy infants, feces of ASD infants had significantly higher and lower abundance of genera Faecalibacterium and Blautia, respectively. Moreover, DNA microarray analysis of peripheral blood mononuclear cells (PBMC) detected more highly than low expressed genes in ASD infants than in healthy infants. Gene Ontology analysis revealed that differentially expressed genes between ASD and healthy infants were involved in interferon (IFN)- γ and type-I IFN signaling pathways. Finally, strong positive correlations between expression of IFN signaling-associated genes in PBMC and fecal abundance of Faecalibacterium were found. Our results strongly suggested that altered gut microbiota in infants resulted from ASD development and was associated with systemic immunity dysregulation, especially chronic inflammation. Graphical abstract: Altered gut microbiota in autistic infants play a role in chronic inflammation induced by interferon signaling that may cause further inflammation in central nervous system.